A Reflection on Arts‐Based Research - Forrest, Michelle (Philosophical Inquiry in Education, 2021)
Concerns are raised regarding the place of the arts in education, specifically as they are used in the social science context of educational research under the title ‘arts-based research’. An examination of Elliot Eisner’s claim that art is research concludes that, though the arts may be used for display, data, or heuristic in educational research, they are not being recognised for their distinctive characteristics. John White’s critique of the theory of multiple intelligences is revisited to mitigate common claims for the arts based upon Gardner. Given the dominance of scientism in today’s research climate, it is argued that the arts should take their rightful place to balance research in its quest for certainty; that they be the antagonist mode of thought called for by John Stuart Mill.